Estradiol mediates vasculoprotection via ERRα-dependent regulation of lipid and ROS metabolism in the endothelium. (October 2015) - Li, Huawen; Liu, Zhaoyu; Gou, Yulan; Yu, Haibing; Siminelakis, Stavros; Wang, Shixuan; Kong, Danli; Zhou, Yikai; Liu, Zhengxiang; Ding, Yuanling; Yao, Dachun
Abstract: The estrogen-mediated vasculoprotective effect has been widely reported in many animal studies, although the clinical trials are controversial and the detailed mechanisms remain unclear. In this study, we focused on the molecular mechanism and consequence of 17β-estradiol (E2)-induced ERRα (estrogen-related receptor alpha) expression in endothelium and its potential beneficial effects on vascular function. The human aorta endothelial cells were used to identify the detailed molecular mechanism and consequences for E2-induced ERRα expression through estrogen receptors (ER), where ERα responses E2-induced ERRα activation, and ERβ responses basal ERRα expression. E2-induced ERRα expression increases fatty acid uptake/oxidation with increased mitochondrial replication, ATP generation and attenuated reactive oxygen species (ROS) formation. We have obtained further in vivo proof from high-fat diet mice that the lentivirus-carried endothelium-specific delivery of ERRα expression on the vascular wall normalizes E2 deficiency-induced increased plasma lipids with ameliorated vascular damage. ERRα knockdown worsens the problem, and the E2 could only partly restore this effect. This is the first time we report the detailed mechanism with direct evidence that E2-induced ERRα expression modulates the fatty acid metabolism and reduces the circulating lipids through endothelium. We conclude that E2-induced ERRα expression in endothelium plays an important role for the E2-induced vasculoprotective effect. Highlights: ERα responses E2-induced ERRα activation, while ERβ responses the basal expression. E2-induced ERRα expression in endothelium reduces the circulating lipids. ERRα expression on vascular wall normalizes E2-deficiency induced vascular function. ERRα knockdown in endothelium increases the blood pressure in high-fat diet mice. E2-induced ERRα expression plays important role in E2-induced vasculoprotective effect.